Ritz Food Corporation - Ponferrada, Regidor (College of Engineering, 2002)
Ritz Food Corporation has been producing different kinds of biscuits, wafers, curls and candies to satisfy the cravings of the Filipinos, young and old alike. Continuous quality improvement of their products as well as their whole system should be applied to be able to maintain their share of the current market. Specifications for the products have to be met to be able to satisfy the customers. Gem biscuits, a product line of Ritz Food Corporation, accounts for the largest total weight of dough used, thus, the study focused on this product. The results of the study can also be well applied to the other products of Ritz. Interview results, histograms and pareto analysis were used to identify the three most occurring problems, which are, crushed biscuits, burnt biscuits and nonconforming thickness. Through tools and techniques in problem analysis, potential causes for these problems were identified. Variables and Attribute Control charts, Process Capability Analysis, Acceptance Sampling Analysis and Quality Cost Analysis were done with the three identified problems. Results show that the occurrence of crushed biscuits appears to be random and there are no assignable causes that could be detected. For the burnt biscuits, it was found that assignable causes for the biscuits being burnt were lapses in the operators or malfunction of the ovens. It was also found out for the third problem, the nonconformity in thickness, that the inherent variability is too large. Recommendations in improvement in the design of processes, materials handling and their statistical quality control were given for each problem. The recommendations and conclusions of this study are for the purpose of helping the company in improving their quality control system. The group recommends the overhauling of oven B. Oven B has been proven to cause a significant number of defects. The group also recommends including the defects caused during shipping and packaging in the documentation. The study also emphasized the relevance of conducting design of experiments in reducing defects of the process. The group also designed a measuring device to be installed with the existing machines to be able to monitor more effectively the thickness of the biscuits.